Navegador GPS para equipamentos móveis com base nos dados cartográficos e elétricos da COPEL - Rebelato, James Gustavo Black (2013)
This work presents the development of a GPS navigator application built over Android platform designed for mobile devices. The main objective of the application is to allow the visualization of vector maps and performing routing calculations related to the data used by the company Copel. The maps are obtained from company database and converted to the standards used by the navigator developed. As a consequence of the work developed during trainee, it was possible to project and implement a proper navigator, which is not based on automotive GPSs, executable on various mobile devices. To perform the study, the following technologies present on academic formation were used: Java programming language, Eclipse development environment, object-oriented programming, database knowledge, analysis and modeling systems. The final goal of deliver a work tool for the company employees was reached by using concepts and techniques for development of mobile applications.